2014
DOI: 10.5610/jaee.14.3_1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tsunami Evacuation Caused by the Great East Japan Earthquake: A Case Study of Ibaraki Prefecture

Abstract: This study characterizes evacuation behavior in Ibaraki Prefecture in the aftermath of the Great East Japan Earthquake and tsunamis based on geographic information, questionnaires, and interview surveys. We identified several factors on which the starting time of evacuation depended, including awareness of evacuation warnings, understanding of anticipated tsunami inundation areas (hazard maps), and distance from anticipated inundation areas. We found that those who were aware of evacuation sites, hazard maps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…People declaring locking houses when they feel ground shaking vary from 14% to 26% (Cerase et al, 2019), but this has reached 52% during the 2014 event (Goto et al, 2020) or 59% during the 2018 event (Harnantyari et al, 2020). During the 2009 Samoa event, 37% declared they were waiting for family news before evacuating, and 24% for neighbors (Lindell, 2015), while 11% evacuated seeing the neighbors running during the 2011 Japan event (Murakami et al, 2012). In the latter study, they also showed that only 3% evacuated when they see an anormal sea movement, while 21% evacuated feeling the ground shaking.…”
Section: But No Clear Trends On the Precise Influence Of Each Stimulu...mentioning
confidence: 96%
See 4 more Smart Citations
“…People declaring locking houses when they feel ground shaking vary from 14% to 26% (Cerase et al, 2019), but this has reached 52% during the 2014 event (Goto et al, 2020) or 59% during the 2018 event (Harnantyari et al, 2020). During the 2009 Samoa event, 37% declared they were waiting for family news before evacuating, and 24% for neighbors (Lindell, 2015), while 11% evacuated seeing the neighbors running during the 2011 Japan event (Murakami et al, 2012). In the latter study, they also showed that only 3% evacuated when they see an anormal sea movement, while 21% evacuated feeling the ground shaking.…”
Section: But No Clear Trends On the Precise Influence Of Each Stimulu...mentioning
confidence: 96%
“…Although ground shaking is not the only warning cue that people can notice before the arrival of a tsunami. Significant water withdrawal may also lead people to evacuate the shore but it may not be sufficient to trigger evacuation by itself (Murakami et al, 2012) and sometimes it does not happen (Bird and Howes, 2008). Feeling both ground shaking and noticing anormal sea movement can provide additional cues to the population and start evacuation movement (Mori et al, 2007).…”
Section: But No Clear Trends On the Precise Influence Of Each Stimulu...mentioning
confidence: 99%
See 3 more Smart Citations